Étude de certains déterminants des incendies volontaires à Montréal - Vallée, Luc; Dupuis, Stéphane (Criminologie, 1997)
Research into the determining factors in arson cases has traditionally focused on factors linked to the characteristics of the burned building. One of our basic hypotheses is that deliberately set fires also have an underlying economic motivation.In this case, the present study confirms the hypothesis that there appears to be an indisputable link between the unemployment rate and mortgage burdens and arson rates, regardless of the phase of the economic cycle in which the arson occurs.Moreover, the study corroborates the idea that increased surveillance is necessary in areas presenting a higher risk of fraud and having a specific socioeconomic and financial profile. A lower incidence of arson and the improvement of insurers ' ability to predict losses due to arson could lead to a significant reduction in the number of claims, and consequently, in the amount of premiums.By looking more specifically at the economic motivations influencing arson throughout the different phases of the economic cycle, this study evokes the establisment of a forecasting system that would allow insurance companies to identify the areas of Montreal that present a higher risk level for arson, thus allowing them to establish their rates in a more equitable manner.